THE “HIDDEN PLEASURES” IN SEAGRAM'S ADVERTISEMENT: THE ART OF PERSUASSION - CAROLINE V. KATEMBA; JOSHUA H.L. TOBING (LPPMPP Institut Seni Indonesia Padangpanjang, 2020)
Advertisement is an art that persuade people to look at it and to get engage as well as be a part of them. There are hidden pleasures in the advertisement that fails to be identified by the costumers that will attract them as they are not aware of it. The purpose of this study is to identify the ‘hidden pleasures” in the Seagram’s advertisement as it aims to seek an answer to these questions: (1). What are the ‘hidden pleasures’(as written) in the Seagram’s advertisement by using semiotic analysis/approach (2). How can these advertisements persuade the viewer? (3). To what group of people does this ad aims at? (target at socio-economic level). Findings are discuss in the paper.